Use of health equity tools in patient safety incident analyses: a scoping review - Michelle Hwang; Phelopater Sedrak; Nazia Sharfuddin; Amir Ginzburg; Kara Ly; Gagandeep Saini; Cynthia Welton; Linda Fan (BMJ Open)
Objectives The aim of this study is to investigate the use and effectiveness of equity tools in current practices of patient safety incident analyses via a scoping review of the literature.Design Scoping review of the literature using the two main search term concepts “health equity” AND “safety review”. The PRISMA-ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews) checklist was used to report in this paper.Data sources Databases including but not limited to MEDLINE, Embase and PubMed were searched from inception to 16 January 2023.Eligibility criteria Studies that included an equity tool in patient safety reviews were included. There were no restrictions on language or setting for included studies. Review articles were excluded.Data extraction and synthesis Two independent reviewers used standardised methods to search and screen included articles. Data from included studies was extracted and compiled.Results Five studies out of 5026 screened studies were included in the final analysis, 4 were conducted in the USA and 1 in Norway. While all studies identified equity domains to guide their approach to the provision of more equitable care, only three proposed change ideas and one implemented their framework to evaluate the role of social determinants and bias in adverse events. Communication was the most common theme found across four of the five studies. Access to healthcare services and bias were included as equity domains in two of the five studies. Implicit bias training was one of the identified change ideas. Other change ideas included improving access and communication, for example, through increasing the use and availability of interpreter services. One of the studies piloted the implementation of their equity checklist and found adverse event causes rooted in equity in 50% of the cases.Conclusions This scoping review demonstrates that there is a gap in current patient safety incident analyses, specifically lacking the consideration of equity domains. The development of a comprehensive health equity tool is necessary to promote equitable and safe care.